(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the pedagogical conditions and methodological opportunities for developing primary school students’ social activity in physical culture lessons. Physical culture in primary education is not limited to the formation of motor skills, physical endurance, coordination, and healthy lifestyle habits; it also creates a meaningful educational environment for developing cooperation, communication, initiative, responsibility, mutual support, discipline, and respect for peers. In physical culture lessons, children enter into active interaction through games, relay races, team exercises, movement tasks, and collective problem-solving situations. These forms of activity help them understand social rules, accept common goals, follow fair play principles, and participate consciously in group processes. The article emphasizes that social activity in younger schoolchildren develops effectively when physical exercises are connected with pedagogical guidance, positive motivation, inclusive participation, and reflective discussion. Special attention is given to the role of the teacher in organizing lesson content in such a way that every child can take part, express initiative, support classmates, and gain experience of socially significant behavior. The study highlights the importance of active games, cooperative tasks, differentiated physical activities, and moral-educational situations in strengthening students’ communicative and social competence.